The new entrepreneur's guide to setting up and running a successful business - Kendall, Paul; Taylor and Francis (Boca Raton, FL : Productivity Press, an imprint of Taylor and Francis, 2018)
There is a lot of political will at the moment to encourage more new startup businesses, with grant funding subsidies, assistance raising finance, exemptions from statutory reporting and tax incentives available to those who are will to take the plunge. There couldn$1 (Bt be a better time for entrepreneurs to take the plunge. This book is written for those considering setting up their own business who have a lot of questions that need answers. While not intended to be a global reference book in respect to accounting, business tax and legislation, this book provides the reader with practical answers to the issues they come across every day. The aim of the book is to provide the new (or future) business owner, with sufficient knowledge to take an active role in the management of their business. It aims to provide them with an insight into the level of knowledge of taxations, general management and the legal framework that the need to successfully run their business. The author includes numerous examples of successes and failures to illustrate the topic from both the UK and the US.s
chapter 1 Introduction -- chapter 2 So You Want to Run Your Own Business -- chapter 3 How Do You Start? -- chapter 4 Buying and Selling a Business -- chapter 5 Staffing -- chapter 6 Taxes and VAT -- chapter 7 Accounts -- chapter 8 Promoting Your Business -- chapter 9 Now You$1 (Bve Got a Successful Business: What$1 (Bs the Next Step? -- chapter 10 How It Can Go Horribly Wrong -- chapter 11 Retirement and Succession. Passing the Business on to the Family upon -- chapter 12 Essentials to Take Away.s
Keywords: Accounting; Advertising; New business enterprises -- Management; New business enterprises; Business, Management and Accounting; Entrepreneurship and Small Business Management; Entrepreneurship; Managerial economics; Small Business Management; Small business -- Management; BUSINESS & ECONOMICS / Small Business; BUSINESS & ECONOMICS / Entrepreneurship